Introducing Lacan - Leader, Darian (Icon Books, 2010)
This series is renowned for its ingenious combination of graphic illustration and intelligent, precise text by leading academics on some of the most challenging subjects around
Previous edition: published as Lacan for beginners. 1995
Keywords: Psychoanalyse; Lacan, Jacques / 1901-1981; Psychoanalysis